Pengembangan Model Pembelajaran Problem Based Learning (Pbl) Terintegrasi Artificial Intelligence Untuk Meningkatkan Literasi Sains Dan Keterampilan Vokasional Siswa - Setria Majuita; Lukman El Hakim; Rizhal Hendi Ristanto (Universitas Serambi Mekkah, 2025)
21st century education demands innovation in learning models that can develop critical thinking, collaborative, creative, and digital literacy skills. In the context of vocational education, particularly chemistry learning in vocational high schools, the main challenges lie in low student engagement and limited application of technology in the learning process. This study aims to examine and develop an Artificial Intelligence (AI)-integrated Problem-Based Learning (PBL) model as an innovative alternative relevant to 21st-century learning needs. The study uses a library research method by examining various scientific sources such as journals, books, and previous research results focusing on the application of PBL and AI in education. The results of the study show that the integration of PBL with AI can improve the effectiveness of chemistry learning in vocational schools through contextual, interactive, and adaptive learning experiences. This model is able to encourage the development of science literacy, vocational skills, and student readiness for work through the application of smart technology in solving real problems. The implementation of this model requires an increase in teachers' capacity in digital literacy and AI-based learning design. It is recommended that vocational schools gradually adopt an AI-based PBL learning approach with the support of teacher training and adequate technological infrastructure in order to realize innovative, effective, and highly competitive chemistry learning in the digital age.